Tagalog verb dictionary - Hawkins, Michael (Michael C.); Gallo-Crail, Rhodalyne (Northern Illinois University Press, 2011)
This handy reference is a concise explanatory text and English-Tagalog/Tagalog-English verb guide designed to address and facilitate the most important aspect of Tagalog language learning--understanding and mastering the complex focal orientation of verbs. It is organized into an accessible pattern illustrating the primary conjugations that establish aspect and actor/object focus for each verb. These verbs are further enhanced by sample sentences demonstrating their usage and introducing common cultural contexts for effective communication. In addition to the verb guide, this text also provides a short history of Tagalog, an extensive explanation of verbal function in the language, and a number of learners' tips intended to ease and expedite the learning process. Taken together, these materials, along with a persistent willingness to engage the language, will facilitate a quick and effective path to fluency. Whether one is studying within the structured environment of a classroom or independently in their spare time, this book is designed to give special attention to the most critical aspects of Tagalog language learning. Tagalog Verb Dictionary's orderly and easily accessible layout and neat size make it the ideal companion for students, travelers, and anyone interested in fast fluency in the language.